FELICITY CONDITIONS IN SPEECH ACT FROM THE “KNIVES OUT” MOVIE: A PPRAGMATIC STUDY - Dianita Dianita; Rivalda Achmad Sofyan (English Journal Literacy Utama, 2023)
This study is entitled "Felicity Conditions in Speech Acts from the "KNIVES OUT" Movie: A Pragmatic Study". The research method used is descriptive qualitative because this research aims to classify, explain and summarize an utterance that appears in a film. The source of the data taken is the utterances that appear in the transcript of the film Knives Out in 2019. Based on the analysis that has been carried out, a total of 45 data types of speech acts have been obtained that consisting in directive action 24 data appear in the film consisting of ordering, commanding, questioning, and requesting forms of speech (53.4%); 8 assertive action data consisting of stating, affirming, asserting (20%); then in commissive action found 7 data consisting of suggest, promise, warn, confirm, offer, and intend (15.5%); and finally, 5 data were found with expressive actions (11.1%) consisting of greeting, condolence, apologies, and thanking; However, in this study, there were no declarations made during the film (0%). Apart from that, the data sources that have been analyzed based on speech acts have fulfilled the conditions of felicity, including the preparatory condition, which contains 19 data (42.3%), Essential Condition 15 data (33.3%), Sincerity Condition 10 (22 .2%), and Propositional Content Condition as much as 1 data (2.2%). From these two discussions, the utterances in the directive action dominate more than the other actions, and the preparatory condition dominates the feeling condition